Chloroplast Genome of Myristica fragrans: Assembly, Annotation, and Phylogenetic Relationships - Hani Sitti Nuroniah; Aditya Nugroho; Fitri Indriani; Eliya Suita; Bakhtiar Basyah; Susanna Susanna; Ujang Wawan Darmawan; Neo Endra Lelana (Forest Science and Technology)
Myristica fragrans is a native and economically significant species in Indonesia. However, its complete chloroplast genome, particularly from Indonesia, has not been previously reported. In this study, we successfully sequenced and assembled the complete chloroplast genome of M. fragrans using next-generation sequencing technology. The genome has a total length of 155,868 bp and exhibits a typical quadripartite structure, consisting of a large single-copy (LSC) region (87,062 bp), a small single-copy (SSC) region (20,664 bp), and a pair of inverted repeats (IRs) (24,071 bp each). Genome annotation identified 126 genes, including 83 protein-coding genes, 8 ribosomal RNA genes, and 35 transfer RNA genes. A total of 141 simple sequence repeats (SSRs) were detected, with mononucleotide repeats being the most prevalent (90.07%). Phylogenetic analysis using six Myristica chloroplast genomes and three outgroup species confirmed that M. fragrans is most closely related to M. argentea, providing new insights into the evolutionary relationships within the Myristicaceae family.